2009
DOI: 10.2967/jnumed.108.059790
|View full text |Cite
|
Sign up to set email alerts
|

The Added Diagnostic Value of Liquid Gastric Emptying Compared with Solid Emptying Alone

Abstract: The medical literature states that solid gastric-emptying studies are more sensitive for the detection of gastroparesis than are liquid studies; thus, liquid studies are rarely required. However, we have seen patients with normal solid but delayed liquid emptying. The purpose of this investigation was to determine whether a study of clear liquid gastric empting has added value for the diagnosis of gastroparesis over a study of solid emptying alone. Methods: A total of 101 patients underwent both solid and liqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
76
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 96 publications
(80 citation statements)
references
References 27 publications
2
76
0
2
Order By: Relevance
“…Liquid GE (usually labeled with indium) is often used to assess postsurgical conditions, as there can be discrepancy in liquid and solid gastric emptying after gastric surgery and/or vagotomy. 3,4 The test involves radiation which is increased with use of simultaneous evaluation of solid and liquid emptying. The technical conduct, choice of collimator, windows for detection of the isotopes, quantitation and corrections of radioactivity for isotope decay and depth, caloric content of the meal, position (upright) and Data analysis and endpoints The percentage retention at 4 h is more reproducible than data acquired during the first 2 h; 8 the 4-h analysis also detects more abnormal GE among symptomatic patients.…”
Section: Study Performancementioning
confidence: 99%
“…Liquid GE (usually labeled with indium) is often used to assess postsurgical conditions, as there can be discrepancy in liquid and solid gastric emptying after gastric surgery and/or vagotomy. 3,4 The test involves radiation which is increased with use of simultaneous evaluation of solid and liquid emptying. The technical conduct, choice of collimator, windows for detection of the isotopes, quantitation and corrections of radioactivity for isotope decay and depth, caloric content of the meal, position (upright) and Data analysis and endpoints The percentage retention at 4 h is more reproducible than data acquired during the first 2 h; 8 the 4-h analysis also detects more abnormal GE among symptomatic patients.…”
Section: Study Performancementioning
confidence: 99%
“…These unresolved issues may cause practitioners to question whether a protocol change is warranted (27). Physicians may not follow guidelines if they think that they are based on poor evidence (28).…”
Section: Guideline Implementationmentioning
confidence: 99%
“…Of patients with normal solid emptying, 32% had delayed liquid emptying. On the basis of these results, these authors suggested that a nonnutrient, liquid GE study may detect fundal gastric dysmotility and help to improve the detection rate of gastric dysmotility in patients with FD (40).…”
Section: Gastric Emptyingmentioning
confidence: 99%